OPTIMALISASI MASALAH PENUGASAN TIDAK SEIMBANG MENGGUNAKAN MODIFIED HUNGARIAN METHOD - EVIPANIA, RENALDO; GANDHIADI, G.K.; SUMARJAYA, I WAYAN (E-Jurnal Matematika; Vol 10 No 1 (2021), 2021)
Assignment problem is one of the cases that found in linear programming. Assignment problem is related to the allocation of workers for available jobs. From several sources, Hungarian method is more often used to solve the assignment problem. In the Hungarian method, if an unbalanced problem is found, the lack of the source or destination will be added to the dummy variable so that the case becomes balanced. The jobs that executed on the dummy machine will be ignored. In real-life situations, it is impossible for companies to ignore existing work because of a lack of workers. Therefore, the Hungarian method is modified to resolve this condition, so that the total assignment cost can still be optimized.